Paedobaptism dan Teologi Perjanjian - Lyly Grace Mantiri (Vieka Wahana Semesta, 2023)
Abstract: In general, Christianity accepts the sacrament of baptism. However, there are differences of opinion regarding: the method, meaning, and the object of baptism. This article specifically discusses two views regarding the object (the recipient) of baptism, namely the views of credobaptism and paedobaptism. In obtaining data and arguments from its adherents, researcher used qualitative method, namely literature studies. After carefully observing and analyzing the data and arguments from both views, the researcher concludes that paedobaptism has a strong basis, especially if understood within the framework of covenant theology. Abstrak: Secara umum, Kekristenan menerima sakramen baptisan. Namun ada perbedaan pendapat tentang: cara, makna, dan objek baptisan. Tulisan ini membahas secara khusus tentang dua pandangan mengenai objek (penerima) baptisan, yaitu pandangan credobaptism dan paedobaptism. Dalam mendapatkan data dan argument dari para penganutnya, peneliti menggunakan metode kualitatif, yakni kajian literatur. Setelah mengamati dan menganalisis secara saksama data dan argumen dari kedua pandangan tersebut, peneliti berkesimpulan bahwa paedobaptism memiliki dasar yang solid, khususnya ketika dipahami dalam kerangka teologi perjanjian.